Research on the Factors of New Media Marketing on the Consumer Behavior of Agricultural Products - Honglei Zhu, Duchun Wang (Forest Chemicals Review)
The outbreak of COVID-19 has promoted the rapid development of the new media marketing model of agricultural products, which has greatly expanded the sales channels of agricultural products. Based on the mature Technology Acceptance Model (TAM) and the theory of Perceived Risk in the field of consumer behavior research, this paper takes the consumers who have received the new media marketing of agricultural products as the research object, and tries to construct the mechanism model of the influence of new media marketing on the consumption behavior of agricultural products.Empirical research shows that platform participation plays a leading role in perceived usefulness and perceived ease of use of agricultural products, followed by usefulness of product, logistics convenience and internet word-of-mouth. Information security plays a leading role in influencing perceived risk, followed by content credibility and platform dependence. Perceived usefulness and perceived ease of use positively affect purchase intention of agricultural products, while perceived risk negatively affect purchase intention of agricultural products. On this basis, the policy and suggestion of promoting the development of new media marketing of agricultural products in China are put forward.